2010
DOI: 10.1111/j.1365-2753.2009.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

A cost simulation for mammography examinations taking into account equipment failures and resource utilization characteristics

Abstract: Discrete-event simulation allowed for the definition of the more efficient clinic, contingent on the expected prevalence of resource utilization and equipment failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…In addition to two previously mentioned studies about increasing vaccine cold storage equipment [47, 91], we identified just nine OR studies related to medical equipment. Some examples include a cost-utility analysis of introducing PET scanning technology for lung cancer diagnosis in Iran [102]; a DES model of a mammography clinic in Brazil that took into account equipment failures and maintenance [103]; a queuing model developed to improve response and turn-around time of equipment repair work orders in a clinical engineering department in Cuba [104]; and models to help inform general medical equipment purchasing [105] and replacement schedules [106] in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to two previously mentioned studies about increasing vaccine cold storage equipment [47, 91], we identified just nine OR studies related to medical equipment. Some examples include a cost-utility analysis of introducing PET scanning technology for lung cancer diagnosis in Iran [102]; a DES model of a mammography clinic in Brazil that took into account equipment failures and maintenance [103]; a queuing model developed to improve response and turn-around time of equipment repair work orders in a clinical engineering department in Cuba [104]; and models to help inform general medical equipment purchasing [105] and replacement schedules [106] in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…CT exams were characterized and divided into stages, each one measured during on-site surveys at CT services in small and average-size hospitals and medical clinics, Brazil. The studied CTs covered all their technological range in the country (1,2,4,16, and 128 slices CTs). Exams were followed in 10 devices of three brands, nine health units, and five cities (three radiological clinics, three general clinics, four general hospitals).…”
Section: Datamentioning
confidence: 99%
“…[1][2][3] However, determining which CT model is the most suitable for a specific setup is not always simple, and numerical methods such as computer simulation may be useful to this end. [4][5][6] Simulations allow for analyzing the behavior of a system without its actual implementation, are widely used in many areas of science, and, increasingly, are used in the modeling of health systems. 7 The objective of this study was to analyze the type of CT scanners most suitable for hospitals of different sizes, contingent on 'hospital scenarios' (structural/organizational changes in hospital resources and exam rates).…”
Section: Introductionmentioning
confidence: 99%
“…Then, adjustments to the model are implemented to understand the effect such changes would have on key performance indicators in a real‐world setting. Common changes DES models consider in a healthcare setting include adding additional staff, 15‐18 beds, 19‐21 or equipment; 11,15 changing scheduling policies; 21‐24 process design; 18,25 layout redesign; 14,26 and the impact of changes in demand 21,27 or discharge rates 28 . The application and value of using such models has been documented extensively 29‐35 …”
Section: Introductionmentioning
confidence: 99%